DNAJC12 and dopa‐responsive nonprogressive parkinsonism. Issue 4 (11th October 2017) - Straniero, Letizia; Guella, Ilaria; Cilia, Roberto; Parkkinen, Laura; Rimoldi, Valeria; Young, Alexander; Asselta, Rosanna; Soldà, Giulia; Sossi, Vesna; Stoessl, A. Jon; Priori, Alberto; Nishioka, Kenya; et al.
Abstract : Biallelic DNAJC12 mutations were described in children with hyperphenylalaninemia, neurodevelopmental delay, and dystonia. We identified DNAJC12 homozygous null variants (c.187A>T;p.K63* and c.79‐2A>G;p.V27Wfs*14) in two kindreds with early‐onset parkinsonism. Both probands had mild intellectual disability, mild nonprogressive, motor symptoms, sustained benefit from small dose of levodopa, and substantial worsening of symptoms after levodopa discontinuation. Neuropathology (Proband‐A) revealed no alpha‐synuclein pathology, and substantia nigra depigmentation with moderate cell loss. DNAJC12 transcripts were reduced in both patients. Our results suggest that DNAJC12 mutations (absent in 500 early‐onset patients with Parkinson's disease) rarely cause dopa‐responsive nonprogressive parkinsonism in adulthood, but broaden the clinical spectrum of DNAJC12 deficiency. Ann Neurol 2017;82:640–646